2019
DOI: 10.1007/s10490-018-9639-z
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of the consequences of servant leadership: The moderating roles of cultural factors

Abstract: The past decade has witnessed growing interests in empirically examining the effectiveness of servant leadership in management research. Our study reviews the literature on servant leadership and analyzes the relationship between servant leadership and outcome variables. Drawing on social exchange theory, this study uses meta-analysis to find that servant leadership is positively related to followers' job-related outcomes (e.g., psychological empowerment, organizational commitment, service quality), leader-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 118 publications
(181 reference statements)
4
84
0
4
Order By: Relevance
“…Lastly, this study provides useful suggestions regarding the creation of a healthy workplace. As pointed out in previous studies ( Lee et al, 2019 ; Zhang et al, 2019 ), organizations should implement, deploy, and support appropriate training development programs for leaders in order to establish reciprocal relationships with their followers and increase their commitment to the organization. The SLS-J and SLS-J-short will provide useful insight for that.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Lastly, this study provides useful suggestions regarding the creation of a healthy workplace. As pointed out in previous studies ( Lee et al, 2019 ; Zhang et al, 2019 ), organizations should implement, deploy, and support appropriate training development programs for leaders in order to establish reciprocal relationships with their followers and increase their commitment to the organization. The SLS-J and SLS-J-short will provide useful insight for that.…”
Section: Discussionmentioning
confidence: 98%
“…Cultural context is assumed to be associated with SL effects ( van Dierendonck, 2011 ; Eva et al, 2019 ). According to thorough analyses, SL has shown a stronger impact when the context involves low power distance, high individualism ( Lee et al, 2019 ; Zhang et al, 2019 ), and low masculinity ( Zhang et al, 2019 ) in terms of Hofstede’s cultural dimensions model ( Hofstede et al, 2010 ). In this study, the SLS-J showed the lowest total score within The Netherlands, United Kingdom, Italy, and Spanish speaking countries, and the highest score of Forgiveness in The Netherlands, United Kingdom, and Italy in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study indicates that the more competent employees perceive their supervisors using a downward influence tactic in the form of consultation, the more they will increase their commitment to supervisors and organizations. Referring to the study context, as in most countries in Asia, respondents are part of a society that tends to have a high power distance value (Zhang et al, 2019). People with a high power distance culture may have high organizational commitment if they experience strong ties with their supervisors as well as paternalistic treatment (Cohen, 2006).…”
Section: Implications For Asian Businessmentioning
confidence: 99%